2016
DOI: 10.1007/s11284-016-1418-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of temperature acclimation on the critical thermal limits and swimming performance of Brachymystax lenok tsinlingensis: a threatened fish in Qinling Mountain region of China

Abstract: Brachymystax lenok tsinlingensis is an endangered teleost fish species that occurs in the Qinling Mountain region of China. It also happens to represent the southernmost distribution of an endemic Salmonid fish worldwide. Recently, the habitat of this species shifted towards a higher altitude presumably because of climate change, indicating that this species might be suffering from thermal stress. However, information on the thermal physiology of this species is extremely limited. Accordingly, we investigated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 59 publications
1
2
0
Order By: Relevance
“…We rejected the hypothesis that temperature acclimation and exercise training affect CoT. Higher acclimation temperatures led to higher CoT in the fish Brachymystax lenok tsinlingensis (Xia et al, 2016). However, that study did not distinguish between acclimation and acute test temperatures, so the temperature effect may have been due to increased acute temperatures, which we also found and which is consistent with other species (Dickson et al, 2002;Lim and Ellerby, 2009).…”
Section: Discussionsupporting
confidence: 52%
“…We rejected the hypothesis that temperature acclimation and exercise training affect CoT. Higher acclimation temperatures led to higher CoT in the fish Brachymystax lenok tsinlingensis (Xia et al, 2016). However, that study did not distinguish between acclimation and acute test temperatures, so the temperature effect may have been due to increased acute temperatures, which we also found and which is consistent with other species (Dickson et al, 2002;Lim and Ellerby, 2009).…”
Section: Discussionsupporting
confidence: 52%
“…Six weeks has been demonstrated to be a sufficient time for protein turnover in muscle, allowing for the detection of acclimation responses in fishes (e.g., Coughlin et al, 2019, 2020; Swank & Rome, 2001; Woytanowski & Coughlin, 2013). Other studies have demonstrated acclimation responses in fish muscle with shorter periods of acclimation (e.g., Watabe, 2002; Xia et al, 2017). All handling of Atlantic salmon was reviewed by the Widener University Institutional Animal Care and Use Committee in accordance with the Guide for Care and Use of Laboratory Animals of the National Research Council (approval number: 2017‐007).…”
Section: Methodsmentioning
confidence: 92%
“…One mechanism to blunt the effects of climate change is thermal acclimation by ectothermic animals such as fishes (Seebacher et al, 2015). Thermal acclimation is a common feature of fishes (Bouchard & Guderley, 2003; Coughlin et al, 2016; James & Tallis, 2019; Johnston et al, 1990; O'Steen & Bennett, 2003; Seebacher & James, 2008; Swank & Rome, 1999, 2001; Wakeling et al, 2000; Woytanowski & Coughlin, 2013) including many species of salmonids (Coughlin et al, 2020; Day & Butler, 2005; Egginton et al, 2000; Evans, 1990; Hvas et al, 2017; MacNutt et al, 2004; Taylor et al, 1996; Xia et al, 2017). Atlantic salmon show limited thermal acclimation of their metabolic function (Hvas et al, 2017), although they do display significant phenotypic plasticity of their cardiac muscle (Anttilla et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…However, due to natural and human factors, such as global warming, environmental destruction, and overfishing, the wild population of this species has declined severely and only 10% of its historical population currently remains. This species was listed as a second-class nationally protected animal in China in 1988 [2,3]. Artificial propagation and release is one effective method by which to restore the wild population of B. tsinlingensis Li.…”
Section: Introductionmentioning
confidence: 99%